MINAT TERHADAP KEBUTUHAN JASA TRANSPORTASI WISATA DI PULAU LOMBOK INDONESIA - Mutiara Lemy, Diena; Rustiani, Agnes (Jurnal IPTA (Industri Perjalanan Wisata); Vol 7 No 1 (2019): Jurnal IPTA (July 2019)DO - 10.24843/IPTA.2019.v07.i01.p06, 2019)
Lombok island is one of the priority destinations of the Special Economic Zone (SEZ) in West Nusa Tenggara, which the government is developing, especially in Kuta Madalika. The number of tourists out of the island of Lombok continued to increase, in 2016 reached 3,094,437 people. This data shows the existence of potential business needs that support tourism, whereas one of them is the need of tourism transportation services. This research was conducted to confirm the interest and need for tourism transportation in the form of buses at Lombok Island. The research study was conducted using a survey method with a questionnaire and supported by interviews. Based on the data collected, it can be concluded that the interests and demands for transportation services for Lombok island. The existence of tourist buses will support the development of tourism in the area.